Counseling and couple therapy for infertile couples - Stammer, Heike; Wischmann, Tewes; Verres, Rolf (Family process, 2004)
The article describes a two-tier, interdisciplinary design for the psychological counseling and therapy of childless couples. It is solution- and resource-oriented and avoids psychopathological ascriptions. Couples are supported in coming to terms with the crisis of a physical disorder and its emotional consequences; they are also aided in developing prospects and options for a future without a biological child. The procedure is explained in detail and provides a model suitable for application at reproduction medicine centers and gynecological and andrological practices. Sample interventions illustrate the therapeutic attitude advocated.
First published: 06 May 2004
Gesehen am 17.02.2021